DETERIORATION QUALITY OBSERVATIONS OF MILK FISH (Chanos chanos FORSK) AND SHORT-BODIED MACKEREL (Rastrelliger neglectus) AT VARIOUS STORAGE TEMPERATURES USING FRESHNESS TESTING PAPER (FTP III) - Tri Winarni Agustini; Titi Surti; S Sumardianto; Dita Setya Wardhani; Ester Kartikasari (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Freshness of fish is crucial in determining the nutritional value and sale value of fishery products.Assessment of fish freshness can be done with various methods based on several principles of chemistry,physics, microbiology, and organoleptic. K value is one of freshness test based on ATP degradation.Analysis of K values can be done with Freshness Testing Paper (FTP III). This method is relativelypractical, easy, fast and the results can be accountable. The material that used in this study are fish milk fish(Chanos chanos Forsk) and short-bodied mackerel (Rastrelliger neglectus) with total 90 fish with anaverage weight of 99 grams / fish (milk fish) and 85 g / fish (short-bodied mackerel). The fish raw materialpurchased from Rejomulyo fish market (Semarang) and taken to the laboratory in a Styrofoam box that wasgiven ice on the inside. This research used an experimental method called descriptive exploration. Storageof samples was handled at different temperatures namely 30oC ± 2oC, 15oC ± 2oC and 1oC ± 0oC. Theobserved parameters include organoleptic test and analysis of K Value (FTP III). The results showed that Kvalues for all samples increased during storage at different temperatures. The highest K values of milk fishand short-bodied mackerel fish during storage at a temperature of 0°C was on 96-hours storage time. Thehighest K values of milk fish and short-bodied mackerel fish during storage at a temperature of 15 ° C wason 72-hours storage time. Whereas the highest K values in milk fish and short-bodied mackerel fish duringstorage at 30°C temperatures, was on the 24-hours storage time. The fastest increase in K value was observed at a temperature of 30°C compared to storage at a temperature of 15°C and 0°C for all the fish samples. This means that the deterioration quality of fish will be faster at high temperatures. K values of mackerel increased more rapidly than milk fish.